Effects of lysozyme combined with cinnamaldehyde on storage quality of olive flounder (Paralichthys olivaceus) fillets. Issue 4 (16th March 2020) - Xu, Yongxia; Yin, Yiming; Li, Tao; Zhao, Honglei; Li, Xuepeng; Li, Jianrong; Sun, Tong
Abstract: Effects of lysozyme (LYS) combined with cinnamaldehyde (CA) on quality enhancement of olive flounder ( Paralichthys olivaceus ) fillets during refrigerated storage at 4 °C for 20 days were assessed. Changes of total viable count (TVC), K ‐value, total volatile basic nitrogen (TVB‐N), thiobarbituric acid (TBA), texture profile analysis (TPA), and trichloroacetic acid‐soluble peptide (TCA‐soluble peptide) in samples were determined periodically. Results demonstrated that the combination of LYS and CA treatment enhanced the antibacterial activity against S. putrefaciens and P. fluorescens, and lowered TVC values. Meanwhile, LYS combined with CA significantly retarded the increases of TBA value, TVB‐N, K ‐value, and TCA‐soluble peptide content compared to the control. Furthermore, the combined treatment also effectively maintained the texture properties of flounder fillets during the storage period. The efficiency was better than that of LYS or CA treatment alone. Thus, LYS combined with CA is promising in olive flounder shelf life extension.